Stepwise construction of dynamic microscale concentration gradients around hydrogel-encapsulated cells in a microfluidic perfusion culture device - Yamahira, Shinya (R Soc Open Sci, 2020)
Inside living organisms, concentration gradients dynamically change over time as biological processes progress. Therefore, methods to construct dynamic microscale concentration gradients in a spatially controlled manner are needed to provide more realistic research environments. Here, we report a novel method for the construction of dynamic microscale concentration gradients in a stepwise manner around cells in micropatterned hydrogel. In our method, cells are encapsulated in a photodegradable hydrogel formed inside a microfluidic perfusion culture device, and perfusion microchannels are then fabricated in the hydrogel by micropatterned photodegradation. The cells in the micropatterned hydrogel can then be cultured by perfusing culture medium through the fabricated microchannels. By using this method, we demonstrate the simultaneous construction of two dynamic concentration gradients, which allowed us to expose the cells encapsulated in the hydrogel to a dynamic microenvironment.